2022
DOI: 10.3390/brainsci12091147
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review Regarding the Modalities to Study Neurodevelopmental Disorders-Like Impairments in Zebrafish—Focussing on Neurobehavioural and Psychological Responses

Abstract: Neurodevelopmental disorders (NDDs) are complex disorders which can be associated with many comorbidities and exhibit multifactorial-dependent phenotypes. An important characteristic is represented by the early onset of the symptoms, during childhood or young adulthood, with a great impact on the socio-cognitive functioning of the affected individuals. Thus, the aim of our review is to describe and to argue the necessity of early developmental stages zebrafish models, focusing on NDDs, especially autism spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…However, further studies regarding these aspects are needed, as the patterns were shown to be dependent on the type, size, and doses of plastic particles used in exposure. Also, the molecular mechanisms underlying the behavioral impairments and their correlation with OS mechanisms could be further studied in the context of plastic NPs/MPs intoxication, since the correlation between two out of the three components of this multifactorial interaction has already described [9,[32][33][34][35][36][37][38][39][40].…”
Section: Behavioral Analysis and Oxidative Stress Responsementioning
confidence: 99%
See 3 more Smart Citations
“…However, further studies regarding these aspects are needed, as the patterns were shown to be dependent on the type, size, and doses of plastic particles used in exposure. Also, the molecular mechanisms underlying the behavioral impairments and their correlation with OS mechanisms could be further studied in the context of plastic NPs/MPs intoxication, since the correlation between two out of the three components of this multifactorial interaction has already described [9,[32][33][34][35][36][37][38][39][40].…”
Section: Behavioral Analysis and Oxidative Stress Responsementioning
confidence: 99%
“…Thus, it has been shown that plastic nano-/microparticles (NPs/MPs) tended to accumulate in the lungs following inhalation from environmental sources [7], or in the gastrointestinal tract of some fish species from waters polluted with plastic NPs/MPs [8]. The severe intoxication of plastic NPs/MPs mainly resulted in immediate negative outcomes, such as organic impairments and tissue damage, as well as long-termed negative effects, such as developmental retardation and defects, chronic inflammation, OS, metabolic imbalance, and mutagenic and teratogenic potential [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations